NOTICE THAT AN ACVA REPRESENTATIVE WILL BE AVAILABLE FOR THE AFL-CIO APPEARANC (Tufts Archival Research Center, 2007)
Confidential; Memo from Susan Stuntz to Tom Donahue regarding availability of an ACVA representative. Describes nature of the meeting- one day question and answer forum with no presentation.